Reconsidering the benefit of intermittent versus continuous treatment in the maintenance treatment setting of metastatic colorectal cancer. (April 2016) - Sunakawa, Y.; Bekaii-Saab, T.; Stintzing, S.
Highlights: We review maintenance treatment in metastatic colorectal cancer. We review current evidence for the clinical benefit of intermittent versus continuous treatment. Fluoropyrimidine plus bevacizumab is a safe and easy to use maintenance strategy. The option of drug a holiday should be discussed with patients not harboring a BRAF mutant tumor. Abstract: Colorectal cancer is one of the most frequent solid tumors in the western world, with low survival rates in patients with metastatic disease. Doublet chemotherapy regimens such as FOLFOX or FOLFIRI are the mainstay of standard first-line chemotherapy in the metastatic setting. The conventional treatment as a first-line approach is continuous application until progression or intolerable toxicities. However, only one third of patients are treated until progression mainly due to the side effects of chemotherapy. Notably, oxaliplatin-containing regimens such as FOLFOX/CapOx or FOLFOXIRI are associated with oxaliplatin-induced neuropathy, which is the main reason for treatment discontinuation or treatment de-escalation. On this basis, recent studies have investigated the clinical benefits of bevacizumab-based intermittent and continuous treatment regimens in the metastatic colorectal setting, together with various strategies to optimize maintenance therapy including regimens with targeted therapies, such as cetuximab, ziv-aflibercept and regorafenib. Recent studies have also investigated when maintenance therapy should be initiated as well individualizing treatment based on patient, tumor and treatment characteristics, as well as molecular biomarkers. This article reviews the current evidence for the clinical benefit of intermittent versus continuous treatment in the maintenance treatment setting of metastatic colorectal cancer, and also evaluates the effect of RAS and BRAF mutational status on maintenance strategies.